Taste Processing: Insights from Animal Models - Molero-Chamizo, Andrés (Molecules, 2020)
Taste processing is an adaptive mechanism involving complex physiological, motivational and cognitive processes. Animal models have provided relevant data about the neuroanatomical and neurobiological components of taste processing. From these models, two important domains of taste responses are described in this review. The first part focuses on the neuroanatomical and neurophysiological bases of olfactory and taste processing. The second part describes the biological and behavioral characteristics of taste learning, with an emphasis on conditioned taste aversion as a key process for the survival and health of many species, including humans.